Quality in the development of the functions of social work: Opportunities and barriers - Arenas-Carbellido, Carmen (The British Journal of Social Work, 2026)
There are difficulties in determining best practices in social work. Often, the environment and organizations promote quality management systems that make it possible to achieve effective and sustainable results. However, the culture of quality has not become widespread in the profession in the Spanish context. This study explores how social work functions can be developed with greater quality from the point of view of professionals. Based on a mixed approach study, it has been possible to contact ninety Spanish social workers with experience in different fields and years of experience in public and private entities. The results show an interest in quality and the existence of barriers or possible areas for improvement that can condition professional work. Among other issues, they point out the need to optimize working conditions, training in quality, and the development of coordination processes. It is recommended to continue to make progress in quality to enable better services for social workers.
Keywords: excellence; evaluation; management; quality; social work